Individual and contextual determinants of social homecare usage in Slovenia - Hlebec, Valentina (Zdravstveno varstvo, 2014)
Theory. Social homecare is important for older people, as it enables them to remain in their own homes during worsening health, thus relieving the burden on institutional facilities such as homes for the elderly or nursing homes and hospitals. Method. A representative survey of social homecare users was employed to assess determinants of the scope of social homecare in Slovenia. Multiple regression analysis was used to evaluate determinants defined by Andersen's behavioral model that affect the scope of social homecare. Results. As expected, need (Functional impairment B = .378, P = 0.000) was the most important explanatory component, followed by availability of informal care network (Lives alone B = -.136, P = 0.000; Has children B = - .142; P = 0.000) and other contextual factors such as total costs of the services (B = -.075; P = 0.003) and temporal availability of services (B=-.075, P=0.012). The model explained 18% of variability in the scope of social homecare. Conclusion. This study showed that data on the individual level, as opposed to data on an aggregated level, show different determinants of social homecare utilization. Moreover, the results showed that social homecare is especially important in two circumstances: when older people have a high level of need and when they do not have access to informal care networks. Contextual factors had a moderate effect on the scope of social homecare, which shows universal access to the latter at the individual level.
Keywords: Community care; Health; Older people; Socialno skrbstvo; Starostniki; Zdravje